Students' Thinking Process in Solving Geometry Problems based on Harel Theory on Malay Traditional House Design - Nirawati, Resy; Rosmaiyadi, Rosmaiyadi; Buyung, Buyung; Kariadi, Dodik (STKIP Singkawang, 2024)
The thinking process is a cognitive development that occurs in the minds of students by involving new knowledge and problems that occur related to geometry concepts to solve problems or find solutions to the problems presented. This study aims to study and describe comprehensively the thinking process of students in solving geometry problems based on Harel theory in the design of Malay traditional houses. This research method is qualitative research with a case study design. Furthermore, the data collection used is observation, tests and interviews. Then for data analysis carried out is reflective analysis with data trustworthiness using the triangulation method. Thefindings in the research of students' thinking processes in solving geometry in the design of Malay traditional houses are the core category / central phenomenon built or constructed by three themes which include mental act, ways of thinking and ways of understanding. Ageometric spec on the design components of West Kalimantan Malay traditional houses includes rectangles, triangles, squares, parallelograms, semicircles, isosceles triangles, right triangles, rhombuses, and trapeziums. The findings in this study need to be implemented in mathematics learning design, which relates to students' experiences in everyday life that touch the realm of local cultural arts so that students become more understanding of the geometry concepts explained so that they can dig deeper into mental acts, ways of thinking and ways of understanding in order to foster various student thought processes in Solve mathematics problems